An Aye Aye for An Aye Aye: Making Biodiversity Offsets Sustainable - Takacs, David (Columbia Journal of Environmental Law, 2020)
In biodiversity offsetting, developers are permitted to degrade an ecosystem and its species in exchange for “offsetting” the damage elsewhere. The practice, albeit controversial, is rapidly spreading as a proposed win-win solution that allows biodiversity and development to coexist. In this article, I explore best practices for how the U.S., Australia, the U.K., and South Africa structure their laws to turn species and their habitats into fungible commodities to be traded like Pokémon cards. I analyze how different jurisdictions regulate the temporal dimension of biodiversity offsetting: when must offset requirements be completed (e.g., before or after the original destruction is allowed), and for how long to must the offset be maintained? I examine the spatial requirements: e.g., how far from the original destruction must or may the offset be? I look at the type of trades that are allowed: for example, must the “replacement” entity be the same as the entity that is destroyed or degraded? Finally, I examine who must do what to make sure the offset is sustained. In analyzing how jurisdictions arrange these variables, I provide examples that others might or might not wish to adapt. Furthermore, how these variables are legally mandated helps us understand how a nation, a state, or a community understands its relationship with the natural world, and what that portends for the future of human/non-human interactions. How polities strike that balance will be reflected by the specific choices they make not only to allow offsetting in the first place, but in the ways they stack the variables to ensure (or not) species and ecosystem viability in the short term and long term. I conclude by explaining how well-structured, carefully implemented and monitored biodiversity offsetting could be part of our conservation toolkit for the Anthropocene era. But to implement biodiversity offsetting in a deeply equitable way will be expensive, difficult, and require a cadre of dedicated stakeholders committed to sustainable human and nonhuman communities.